Regulation of immune and nonimmune mast cell activation by phenols from olive oil - Penissi, Alicia Beatriz (2019)
The purpose of this study is to establish if hydroxytyrosol and oleuropein, themost significant phenols found in olive oil and olives, can inhibit the activation of mast cells induced by immune and nonimmune pathways. Preincubation of purified peritoneal mast cells was carried out in the presence of hydroxytyrosol or oleuropein compounds and, prior to incubation, with concanavalin A, compound 48/80, or calcium ionophore A23187. Dose-response and time-dependence were studied. Comparative studies were performed using sodium cromoglycate, a well-known mast cell stabilizer. The supernatants and pellets were analyzed for β-hexosaminidase content via colorimetric reaction after incubation. The percentage of β-hexosaminidase obtained in each tube was measured and taken as a referent mast cell activation indicator. Other cell pellet samples were studied for cell viability, by means of the trypan blue exclusion method, or analyzed with light and electron microscopy. For the first time, biochemical and morphological results have shown that hydroxytyrosol and oleuropein inhibit degranulation of mast cells triggered by both immune and nonimmune causes. These findings suggest that olive phenols, specifically hydroxytyrosol and oleuropein, may be set the bases for developing practical tools not only to prevent and treat mast cell-mediated disorders butalso to improve olive oil industrialization.